2022
DOI: 10.3390/machines10090806
|View full text |Cite
|
Sign up to set email alerts
|

Design and Optimization of the Surface Texture at the Hydrostatic Bearing and the Spindle for High Precision Machining

Abstract: Hydrostatic bearing spindles are widely applied in high precision grinding and turning machines due to their good dynamic stability and rotational accuracy. However, under the condition of high-speed rotations, the heat generated by the friction of the oil film will cause the shear thinning effect. It not only reduces the rotation accuracy of the spindle but also reduces the service life of the spindle. The surface texture structure and configuration between the planes play the role of homogenizing oil film te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The solid abrasive enclosed in a starch agglomeration structure is used to micro-cut the surface microstructure of the optics as the main component of the CFP removal mechanism. Before the CFP, the compliant figuring tool was initially finished on a self-designed six-axis figuring machine requiring a high-precision hydrostatic spindle [34]. It is a compressible and suitable sub-diameter tool shown as Fig.…”
Section: Fig 3 Schematic Diagram Combined Process Of Spdt and Cfpmentioning
confidence: 99%
“…The solid abrasive enclosed in a starch agglomeration structure is used to micro-cut the surface microstructure of the optics as the main component of the CFP removal mechanism. Before the CFP, the compliant figuring tool was initially finished on a self-designed six-axis figuring machine requiring a high-precision hydrostatic spindle [34]. It is a compressible and suitable sub-diameter tool shown as Fig.…”
Section: Fig 3 Schematic Diagram Combined Process Of Spdt and Cfpmentioning
confidence: 99%
“…Ran HF used the Roelands equation to consider the changes in viscosity, temperature, turbulence, and cavitation and researched the cavitation area of hydrostatic thrust bearing with spiral angle, slot width ratio, rotational speed, and other parameters [16]. Shang YY studied the influence of surface texture shape and height on the bearing performance of hydrostatic thrust bearing and established the change rule of bearing performance under the change of oil supply pressure according to the viscosity-temperature characteristics of lubricating oil [17,18]. Novotný P combines lubrication and heat transfer models to optimize the structure of circular thrust bearings based on genetic algorithms, reducing friction losses by about 30% [19].…”
Section: Introductionmentioning
confidence: 99%
“…Feng Yufangli studied the improved quantum bee colony algorithm used to optimize the structural parameters of each layer of BP neural network, which can effectively improve the fault diagnosis efficiency of rolling bearings [22] . Shang Youyun systematically investigated the influence of the surface texture shape and height on the thrust bearing performance of the hydrostatic spindle by comparative analysis, and developed CFD simulations to analyze the computational results based on the theory of viscosity-temperature characteristics [23] . Comprehensive research on surface texture and BP neural networks at home and abroad can be found that in recent years, many scholars have become more mature in the study of surface texture, but the determination and optimization of surface texture size parameters are not particularly in-depth, and the application of BP neural network in the optimization of surface texture is less.…”
Section: Introductionmentioning
confidence: 99%